“Like journeying through a painting”: Travel Writing and the Exploration of Textual Boundaries in Rachel Cusk’s The Last Supper - Isabelle RANNOU (E-REA)
Presenting itself as the account of a journey undertaken with her family, Rachel Cusk’s The Last Supper, A Summer in Italy echoes other works of travel writing as it questions the verbal translation of the lived experience. The author, who chooses a landmark of aestheticism as her destination, sets out to ponder the subtle relation between creation (through repeated references to the history of art) and the representation of the everyday. Punctuating the written recollection of the travels, several reproductions of paintings and holiday snapshots seem to prolong Cusk’s attempt to capture the transitory nature of the ordinary while allowing the reader to assess the respective powers of the narrative and its visual illustrations to do so. The resulting collaboration of the verbal and visual mediums delineates another quest of the text which, beyond exploring the formal devices of the genre, eventually celebrates the figure of the artist.